2013
DOI: 10.1002/cjoc.201300550
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of CO2 Solubility in Polymers by Radial Basis Function Artificial Neural Network Based on Chaotic Self‐adaptive Particle Swarm Optimization and Fuzzy Clustering Method

Abstract: To replace costly and time-consuming experimentation in laboratory, a novel solubility prediction model based on chaos theory, self-adaptive particle swarm optimization (PSO), fuzzy c-means clustering method, and radial basis function artificial neural network (RBF ANN) is proposed to predict CO 2 solubility in polymers, hereafter called CSPSO-FC RBF ANN. The premature convergence problem is overcome by modifying the conventional PSO using chaos theory and self-adaptive inertia weight factor. Fuzzy c-means clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The main key to a successful implementation of RBFNN is to find three important parameters: the hidden centres, the radius (spread) of each RBF function in each dimension and the number of neurons …”
Section: Resultsmentioning
confidence: 99%
“…The main key to a successful implementation of RBFNN is to find three important parameters: the hidden centres, the radius (spread) of each RBF function in each dimension and the number of neurons …”
Section: Resultsmentioning
confidence: 99%
“…25,29 Differing from universal approximation neural networks, such as a multilayer perceptron, RBF employs specic radial basis functions in hidden layer nodes to realize nonlinear mapping. 25,29 Differing from universal approximation neural networks, such as a multilayer perceptron, RBF employs specic radial basis functions in hidden layer nodes to realize nonlinear mapping.…”
Section: Radial Basis Function Articial Neural Network (Rbf Ann)mentioning
confidence: 99%
“…where w ik is the ith-row kth-column element in the matrix W. Previous studies 25,29,30,33,35 indicated that empirical formula and heuristics were generally adopted to optimize and determine the number of hidden layer nodes. Therefore, a batch operation parameter training method was used to train the RBF in this study.…”
Section: Radial Basis Function Articial Neural Network (Rbf Ann)mentioning
confidence: 99%
“…In recent years, dissolution calculation models have been widely considered and mainly include traditional models based on mathematical theory and computational models based on information technology [12,[16][17][18][19][20][21][22]. Mathematical models mainly include thermodynamic equation of state models and empirical/semi-empirical models.…”
Section: Introductionmentioning
confidence: 99%